ST IES ON LENG IGHT RELATIONSHIPS OF GERRES FILAMENTOSUS CUVIER FROM THE ESTU IES OF T I SOUTHEKN r:ARNAT COAST* - Udupa, K. S.; Averel, M.; Raghavendra, C. H.; Bevinahalli, Vinayak; Reddy, Ashwath; Kumarswamy, A. R. (Journal of Indian Fisheries Association, 2016)
Random samples of Gerres filamentosus Cuvier from the Netravathi- Gurpur, Mulky, Kallayanapura, Mabukala and Kundapura estuaries of the southern Karnataka Coast were collected in the years 2000, 2001 and 2002, and length-weight relationships for each estuary were derived using multiple linear regression technique with one dummy variable. Hence, combined or sex-wise length-weight relationships were obtained after testing for homogeneity and isometric growth condition of fishes for each estuary by ttest. The extent of closeness of length-weight relationships between sexes and among estuaries for different years is explained by a trend line graph. The whole process of multiple linear regression analysis with one dummy variable is a better substitute for the analysis of covariance technique. Keywords: Gerres filamentosus, estuaries, length-weight relationships, multiple linear regression technique